Human croquet - Atkinson, Kate. (London : Black Swan, 1998)
Explores the life and times of the Fairfax family of England through the eyes of sixteen-year-old Isobel who discusses a brother who fears alien abductions, an aunt obsessed with cats, and a stepmother who suffers from hallucinations.
Adult.
Keywords: Family -- England -- Fiction; Youth -- England -- Fiction; Family life -- Fiction; Youth -- England -- Fiction; England -- Fiction; England -- Fiction